(untitled) (Asian Business Research, 2026)
Entrepreneurship bricolage is an important way for entrepreneurs to dynamically tap and use existing resources to achieve the purpose of entrepreneurial activities based on the entrepreneurial context. The research on the result effect, driving factors and mechanism of entrepreneurship bricolage in different entrepreneurial contexts can provide a new perspective for the effective use of resource endowments for entrepreneurial enterprises. A systematic analysis of 115 documents collected in the field of entrepreneurial bricolage in recent years found that the driving factors of entrepreneurial bricolage from the perspective of different entrepreneurial contexts differ depending on the growth stage and resource endowment status of the enterprise; There are differences in the mechanism of entrepreneurial bricolage from the perspective of different entrepreneurial contexts in the macro entrepreneurial environment, the meso entrepreneurial organization, and the micro entrepreneurial individual; The effect of entrepreneurial bricolage from the perspective of different entrepreneurial contexts is different in two aspects about research theme and research purpose. The research conclusions are helpful for domestic scholars to put forward countermeasures and suggestions to promote the high-quality development of regional innovative and entrepreneurial enterprises based on the current status of research in the field of entrepreneurial bricolage, combined with factors such as China’s current economic background and entrepreneurial situation differences.